The evolution of ambiguity in sender-receiver signaling games - Roland Mühlenbernd; Sławomir Wacewicz; Przemysław Żywiczyński (Games, 2022)
We study an extended version of a sender-receiver signaling game-a context-signaling (CS) game that involves external contextual cues that provide information about a sender's private information state. A formal evolutionary analysis of the investigated CS game shows that ambiguous signaling strategies can achieve perfect information transfer and are evolutionarily stable. Moreover, a computational analysis of the CS game shows that such perfect ambiguous systems have the same emergence probability as non-ambiguous perfect signaling systems in multi-agent simulations under standard evolutionary dynamics. We contrast these results with an experimental study where pairs of participants play the CS game for multiple rounds with each other in the lab to develop a communication system. This comparison shows that unlike virtual agents, human agents clearly prefer perfect signaling systems over perfect ambiguous systems.
Keywords: 330; ambiguity; contextual cues; evolutionary stability; imitation dynamics; online experiments; sender-receiver signaling games